Mediation effects of capital structure and profitability: liquidity on company value - Laksmiwati, Mia; Meidiyustiani, Rinny; Priyanto, Sugeng; Arisudhana, Dicky (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the effect of liquidity on company value which is moderated by capital structure and profitability in companies that are members of the Jakarta Islamic Index during the 2018 - 2022 period. The data analysis technique used in this research uses the Partial Least Square (PLS) approach using Smart software. PLS. The research results show that CR has a significant effect on both DER and ROE. However, CR has no effect on PBV, meaning that fluctuations in CR have no impact on the rise and fall of PBV. The DER level has no effect on PBV and ROE has a positive effect on PBV. Capital structure and profitability are able to moderate liquidity on company value. This research has the implication that companies must always pay attention to the level of profitability because this is the main consideration for potential investors when deciding to invest in shares. Meanwhile, liquidity can influence company value but not directly, so an evaluation must be carried out and determine policies to optimize this value so that its contribution to increasing company value is greater.